Understanding Recruitment Yield From Social Media Advertisements and Associated Costs of a Telehealth Randomized Controlled Trial: Descriptive Study - Jéssica Bianca Aily; Jennifer Copson; Dana Voinier; Jason Jakiela; Rana Hinman; Megan Grosch; Colleen Noonan; Megan Armellini; Laura Schmitt; Mika White; Daniel White (JMIR Publications, 2023)
BackgroundRecruiting study participants for clinical research is a challenging yet essential task. Social media platforms, such as Facebook, offer the opportunity to recruit participants through paid advertisements. These ad campaigns may be a cost-effective approach to reaching and recruiting participants who meet specific study criteria. However, little is known about the extent to which clicks on social media advertisements translate to the actual consent and enrollment of participants who meet the study criteria. Understanding this is especially important for clinical trials conducted remotely, such as telehealth-based studies, which open the possibility to recruit over large geographical areas and are becoming more common for the treatment of chronic health conditions, such as osteoarthritis (OA). ObjectiveThe aim of this study was to report on the conversion of clicks on a Facebook advertisement campaign to consent to enrollment in an ongoing telehealth physical therapy study for adults with knee OA, and the costs associated with recruitment. MethodsThis was a secondary analysis using data collected over the first 5 months of an ongoing study of adults with knee OA. The Delaware Physical Exercise and Activity for Knee Osteoarthritis program compares a virtually delivered exercise program to a control group receiving web-based resources among adults with knee OA. Advertisement campaigns were configured on Facebook to reach an audience who could be potentially eligible. Clicking on the advertisement directed potential participants to a web-based screening form to answer 6 brief questions related to the study criteria. Next, a research team member called individuals who met the criteria from the screening form and verbally asked additional questions related to the study criteria. Once considered eligible, an electronic informed consent form (ICF) was sent. We described the number of potential study participants who made it through each of these steps and then calculated the cost per participant who signed the ICF. ResultsIn sum, between July and November 2021, a total of 33,319 unique users saw at least one advertisement, 9879 clicks were made, 423 web-based screening forms were completed, 132 participants were successfully contacted, 70 were considered eligible, and 32 signed the ICF. Recruitment costed an average of US $51.94 per participant. ConclusionsWhile there was a low conversion from clicks to actual consent, 32% (32/100) of the total sample required for the study were expeditiously consented over 5 months with a per-subject cost well below traditional means of recruitment, which ranges from US $90 to US $1000 per participant. Trial RegistrationClinicaltrails.gov NCT04980300; https://clinicaltrials.gov/ct2/show/NCT04980300